Transient multi-Fickian hygro-mechanical analysis of wood. (15th February 2018) - Konopka, Daniel; Kaliske, Michael
Highlights: Mechanics and two-phase moisture diffusion coupled in monolithic solution algorithm. Moisture dependent mechanical and hygrical material characteristics. Transient simulations of three-dimensional specimens at hygro-mechanical loading. Analysis of hygro-mechanical behaviour in elastic and plastic short-term range. Comparison of stresses and moisture to commonly used single-phase diffusion models. Application ranges and recommendations for the diffusion models. Abstract: A new hygro-mechanically coupled material model to simulate the structural behaviour of wooden objects below the fibre saturation area is introduced. A multi-Fick ian moisture transport model is coupled to a moisture-dependent, orthotropic, elasto-plastic, mechanical material model. It is applied to wooden specimens at simulated climate changes of the ambient air and analysed by the finite element method with respect to internal stresses due to swelling and shrinkage. A simulation of the ductile failure of a swelling pressure experiment is presented. The results are compared to different, widely used moisture transport models. The importance of capturing water vapour diffusion inside the object and its emissivity at the objects' surface are discussed.